Perceived employability of highly skilled migrant women in STEM: Insights from labor market intermediaries' professionals - Aurora Ricci; Francesca Crivellaro; Daniela Bolzani (Administrative Sciences, 2021)
While global economies are in a tremendous need for talented workers that could fill vacancies in Science, Technology, Engineering, and Mathematics (STEM) fields, available evidence shows that highly skilled migrants with a background in these fields are not protected from brain waste and deskilling. In this paper, we add to the previous literature on the employability of highly skilled migrant women from the specific - and under-investigated-perspective of labor market intermediaries. We specifically investigate what the barriers and resources are for employability of highly skilled migrant women in STEM, as perceived by labor market intermediaries' professionals; and what the training needs are that labor market intermediaries' professionals perceive to effectively work with this target group. We use unique explorative survey data collected in 2018 in five countries (Greece, Hungary, Italy, Sweden, United Kingdom) from professionals working in diverse labor market intermediary organizations. We find that these professionals perceive the employability of migrant women in STEM as rather low, and strongly determined by migrant women's psychological capital. Professionals in Southern Europe perceive structural barriers as more important than those in other countries. Professionals display training needs related to ad-hoc mentoring and networking competences for this specific target group. We discuss theoretical and practical implications.
Keywords: 350; highly skilled migration; highly skilled migrants; international migrants; labor market intermediaries; women; gender and Europe